PEMBELAJARAN FIQIH KONTEKSTUAl PESANTREN DI KOTA BEKASI (ANALASIS DIALEKTIKA TEKS DAN KONTEKS) - Muhamad Ibrohim; Nabil Nabil (Almarhalah, 2021)
Pesantren and the kitab kuning are two inseparable sides of Islamic education in Indonesia. Since its early history, pesantren could not be separated from the literature of the book of thoughts of the salaf scholars which began around the 9th century. It could be said that without the existence and teaching of the yellow book, an educational institution would not legally be called a pesantren. Those are the facts that surfaced in the field. Contextual learning is a holistic educational process and aims to motivate students to understand the meaning of the subject matter they are learning by linking the material to the context of their daily life (personal, social, and cultural context) so that students have knowledge or skills that can be flexibly applied from one problem to another. The most basic idea of this model is that students need to get used to solving problems, find something useful for themselves, and wrestle with the ideas they get from the learning material.